On the Molecular Mechanism of a Photo‐Responsive Phase Change Memory. Issue 5 (2nd April 2021) - Amirjalayer, Saeed
Abstract: Inducing well‐defined transitions by external stimuli between different states of matter is at the core of responsive functional materials. Using light to interconvert between states with distinct and externally readable features such as optical properties, these photo‐responsive phase change materials (PCMs) are ideal candidates for photonic applications. In this context, correlating macroscopic phenomena with properties at the atomistic level is crucial to systematically tailor the performance of PCMs. In particular, to establish a bottom‐up strategy to engineer PCMs based on molecular building units, a detailed understanding of the dynamic properties is needed. Therefore, an atomistic study is reported capturing the structural evolution during the light‐induced phase transition of a tetra‐(azobenzene)‐methane based PCM. This out‐of‐equilibrium dynamics is accurately represented by an atomistic potential, developed using a population swapping genetic algorithm. The molecular mechanism of the phase transition is deciphered and the refractive index of the periodic matrix is investigated. Due to an interplay of structural rigidity and flexibility, already small structural rearrangements lead to alteration of the optical properties, which is fundamental to ensure high data‐transfer rates. By correlating molecular properties with the resulting functionality, the reported work provides an important step towards in silico engineering of photo‐responsive PCMs. Abstract : Light‐induced structural transformation of a molecular‐based phase change material is disclosed at the atomic level. This molecular insight reveals that only small structural rearrangements within the periodic matrix, conserving the overall material topology, are needed to change the optical properties, which is fundamental for high data‐transfer rates in photonic applications.